Effect of mixing feed of rougher with its last five cells concentrate on performance of flotation circuit at the Sarcheshmeh copper concentrator plant No. 1, A. Noury, F. Nakhaei, and S. Ghodrati - A. Noury; F. Nakhaei; S. Ghodrati (The Southern African Institute of Mining and Metallurgy, 2020)
To achieve maximum efficiency in any purification stage, the flotation should be continued until the concentrate grade reaches the feed grade. During sampling from rougher cells of the Iranian Sarcheshmeh copper concentrator plant 1, it was revealed that the concentrate grade of the last five cells of rougher circuit was close to feed grade. Therefore, it was suggested that the concentrate of the aforementioned cells be mixed with rougher feed. In this study, one of eight rougher circuit rows was selected and evaluated. The floatability tests were performed to compare the flotation behaviour of rougher feed and mixture of concentrate of the last five cells with rougher feed in the laboratory scale by a tree analysis process. The results showed that mixing of rougher last five cell concentrate with feed has a detrimental effect on flotation efficiency that leads to a 3% decrease in recovery. It was also observed that with grinding of this concentrate, recovery can be improved. Keywords: Efficiency, flotation, rougher, tree analysis, floatability, concentrate, mixing